Vloga malih RNK pri odzivu rastlin na okužbo s patogenimi organizmi - Kunej, Urban (Acta agriculturae Slovenica, 2022)
Plants have evolved diverse and complex mechanisms to regulate gene expression. Recently, a new mechanism called RNA interference (RNAi) has been discovered. At the core of RNAi are small non-coding RNAs (sRNAs), 21-24 nucleotides in length, that prevent the translation of transcripts into proteins by binding to complementary sites in transcripts. Because sRNAs are determined by origin, precursor structural properties, and sequence characteristics, they are classified into several classes like microRNAs (miRNAs) and secondary small interfering RNAs (siRNAs), which include tasiRNAs and phasiRNAs. They play important roles in regulating gene expression in a wide range of biological processes and in plant responses to biotic or abiotic stresses. Despite the numerous conserved sRNAs among plant species and the characterization of their function, there is still no comprehensive understanding of their role in plant defense responses against phytopathogens. This review summarizes the current understanding of Verticillium wilt pathogenesis, plant defense mechanisms against phytopathogens, and the biogenesis and roles of miRNAs, tasiRNAs, and phasiRNAs in plant defense responses against fungal pathogens. Further studies on plant sRNAs and their expression in response to various phytopathogens are needed to clearly define their roles. New sequencing approaches, bioinformatic analysis, and prediction of the role of miRNA targets during infection may allow us to develop new forms of plant protection in non-model organisms.
Keywords: biotic stress; biotski stres; male RNK; microRNA; mikroRNK; pathogens; patogeni; small RNAs; Verticillium nonalfalfae